Technology and Modeling of Nonclassical Transistor Devices. (3rd November 2019) - Angelov, George V.; Nikolov, Dimitar N.; Hristov, Marin H.
Abstract : This paper presents a comprehensive outlook for the current technology status and the prospective upcoming advancements. VLSI scaling trends and technology advancements in the context of sub-10-nm technologies are reviewed as well as the associated device modeling approaches and compact models of transistor structures are considered. As technology goes into the nanometer regime, semiconductor devices are confronting numerous short-channel effects. Bulk CMOS technology is developing and innovating to overcome these constraints by introduction of (i) new technologies and new materials and (ii) new transistor architectures. Technology boosters such as high- k /metal-gate technologies, ultra-thin-body SOI, Ge-on-insulator (GOI), A III –B V semiconductors, and band-engineered transistor (SiGe or Strained Si-channel) with high-carrier-mobility channels are examined. Nonclassical device structures such as novel multiple-gate transistor structures including multiple-gate field-effect transistors, FD-SOI MOSFETs, CNTFETs, and SETs are examined as possible successors of conventional CMOS devices and FinFETs. Special attention is devoted to gate-all-around FETs and, respectively, nanowire and nanosheet FETs as forthcoming mainstream replacements of FinFET. In view of that, compact modeling of bulk CMOS transistors and multiple-gate transistors are considered as well as BSIM and PSP multiple-gate models, FD-SOI MOSFETs, CNTFET, and SET modeling are reviewed.